Implementation of Microcontroller-Based Current Speed Monitoring System - Rachel Cristin Hutasoit (Brilliance: Research of Artificial Intelligence, 2022)
In this research, the designed system consists of two parts. First, the hardware consists of a power supply, display, optocoupler sensor, LCD and mechanical measuring instrument. The microcontroller used is ATMega 8535 which serves as a controller. The software used on the microcontroller chip functions to read, process data received from the input port and send the processed data through the output port. On the ATMega8535 microcontroller, the system has been designed with an accuracy rate of 97%, precision 96%, error 3.8%, the resolution of the measuring instrument can be used as a measurement reference. Additional software used is a delogger, which is set to read the river current velocity every minute, which is stored every 10 minutes.